A new species of Dolichopus Latreille, 1796 (Diptera: Dolichopodidae) from Japan - O.O. Maslova; O.P. Negrobov; V.N. Fursov (Кавказский энтомологический бюллетень, 2014)
The new species from Japan Dolichopus kumazawai Maslova, Negrobov et Fursov, sp. n. is described. The species is close to Dolichopus vaillanti Parent, 1927 and can be distinguished from latter by wings without stigma, postpedicel 1.7 times greater than its width, hind basitarsus mostly yellow.